Malaysian internal auditor’s risk judgment performance: examining the impact of ISA 610 “using the work of the internal auditor”/ Fazlida Mohd Razali … [et al.] - Mohd Razali, Fazlida; Ilias, Azleen; Johari, Razana Juhaida; Suntharanurak, Sutthi; Ibrahim Acis, Norizelini (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2022)
Effective from December 2016, the Malaysian external auditor is required under the revision of the International Standard on Auditing (ISA) to give comments on Key Audit Matters (KAM) in the audit client’s financial statement which indirectly increases the relevancy of ISA 610 “Using the Work of Internal Auditor”. This study aimed to explore the impact of two main aspects under ISA 610 namely “external auditor engagement quality (EX_QUAL)” and “external auditor reliance (EX_RELY)” on internal auditor’s risk judgment performance. The survey of 274 internal auditors in the Malaysian public and private sector found that internal auditors who experienced high EX_QUAL outperform risk judgment as a result of awareness that the judgment made must be reflective of their own competency, independence, work performance and due care. Unfortunately, internal auditors who experienced high EX_RELY did not perform as expected since internal auditor’s anxieties on the bad consequences of full disclosure risk faced by the company. EX_QUAL could be one of monitoring mechanism to improve internal audit’s risk judgment. Furthermore, mitigating action, such as external auditor involvement in internal audit annual risk assessment plan could deter internal auditor bias and increase objectivity, and thus induce a positive impact of EX_RELY on internal auditor’s risk judgment performance.